Antituberculotic Chemotherapy-General and Hepatic Toxicity Revisited - Ali Akbar Sial, Aisha Jabeen, Talha bin Fayyaz, Maria Muneer, Rabia Bushra, Nusrat Bano, Mirza Tasawer Baig (Journal of Applied Pharmaceutical Science, 2014)
Severe or pertinent hepatic toxicity interferes with antituberculotic chemotherapy resulting in dose reductions, treatment delays or cessation of therapy. Hepatic toxicity by antituberculotic agents is due to anaphylactic reactions (acetylaor phenotype polymorphism) and is relative to the cumulative dose intensity. Risk of hepatic toxicity is higher in the elderly and alcoholic patients. Patients with previous hepatic diseases such as hepatitis and comorbidities i.e. HIV infections, malnutrition and renal damages are prone to an added risk of hepatic toxicity. This review consolidates the pattern of hepatic adverse effects associated with each component of the antimyobacterial regimen e.g. isoniazid, rifampicin and pyrazinamaide. Higher propensities of hepatic adverse effects are associated with the first line agents, intensified by the incorporation of second line antibiotics, primarily metabolized in the liver. In conclusion the hepatic biomarkers should be monitored in the patient under a tuberculosis treatment plan as well as purposefully assessed during follow-up visits of the patients.
Keywords: Antituberculotic Chemotherapy, Hepatic Toxicity, isoniazid, rifampicin and pyrazinamaide.